Prevalence and Outcomes of COVID-19 Among Patients With Inflammatory Bowel Disease—A Danish Prospective Population-based Cohort Study. (9th October 2020) - Attauabi, Mohamed; Poulsen, Anja; Theede, Klaus; Pedersen, Natalia; Larsen, Lone; Jess, Tine; Rosager Hansen, Malte; Verner-Andersen, Marianne Kajbæk; V Haderslev, Kent; Berg Lødrup, Anders; Molazahi, Akbar; Neumann, Anders; et al.
Abstract: Background and Aims: As no population-based study has investigated the susceptibility and disease course of COVID-19 among patients with inflammatory bowel diseases [IBD], we aimed to investigate this topic in a population-based setting. Methods: Two cohorts were investigated. First, a nationwide cohort of all IBD patients diagnosed with COVID-19 was prospectively followed to investigate the disease courses of both diseases. Second, within a population-based cohort of 2.6 million Danish citizens, we identified all individuals tested for SARS-CoV-2 to determine the occurrence of COVID-19 among patients with and without IBD and other immune-mediated inflammatory diseases [IMIDs]. Results: Between January 28, 2020 and June 2, 2020, a total of 76 IBD patients with COVID-19 were identified in the national cohort and prospectively followed for 35 days (interquartile range [IQR]: 25–51). A large proportion [ n  = 19: 25%] required a COVID-19-related hospitalisation for 7 days [IQR: 2–8.5] which was associated with being 65 years or older (odds ratio [OR] = 23].80, 95% confidence interval [CI] 6.32–89.63, p  <0.01) and presence of any non-IMID comorbidity [OR = 8.12, 95% CI 2.55–25.87, p  <0.01], but not use of immunomodulators [ p  = 0.52] or biologic therapies [ p  =   0.14]. In the population-based study, 8476 of 231 601 [3.7%] residents tested positive for SARS-CoV-2; however, the occurrence was significantly lower among patients with IBD [62 of the 2486 patients = 2.5%, p  <0.01] and other IMIDs [531 of 16 492 patients = 3.2%, p  <0.01] as compared with patients without IMIDs. Conclusions: Patients with IMIDs, including IBD, had a significantly lower susceptibility to COVID-19 than patients without IMIDs, and neither immunosuppressive therapies nor IBD activity were associated with the disease course of COVID-19.